Preliminary Discussion of Perspectives on Experimentation Product Development: A Case Study of Product Development in the Retail Industry - Ryuma UMEKI (AAOS Transactions)
In this paper, I analyze “experimentation” which has recently been the focus of much attention in product development, using a grounded theory approach. In previous studies of experimentation, there have been two perspectives. The first is a study to clarify the organizational climate required for experimentation. Second, there have been studies that have clarified how the tools used in experimentation enhance the effectiveness of experimentation. However, few studies have considered the effects of the tools used in experimentation on the organizational climate. Therefore, this study argues that it is necessary to discuss the effects of the tools used in experimentation on the organizational climate. This is because the tools used in experiments have an effect not only on the experimentation itself but also on the actors who conduct the experiments. Two hypotheses were generated as a result of considering the effects of the tools of experimentation on organizational climate. The first is that the tools of experimentation make the members of the organization more willing to conduct experiments by reducing the cost and time required to conduct one experimentation. The second is that the existence of the experimentation tool puts pressure on the organization to conduct the experimentation.